Digital Transformation of the Consulting Industry Extending the Traditional Delivery Model (Progress in IS,, 2018)
This book discusses the opportunities and conditions that digital technology provides to extend, innovate and differentiate the services offered by consulting companies. It introduces suitable artefacts like web-based consulting platforms, consulting applications, semantic technologies and tools for data mining and collaboration. Furthermore it examines concepts to evaluate the virtualization of consulting processes and showcases how solutions can be developed to blend traditional and digital consulting models. Presenting state-of-the-art research and providing a comprehensive overview of the methods and techniques needed for digital transformation in the consulting industry, the book serves as both a guide and a roadmap for innovative consulting companies.